KEMADIRIAN PAKAN BERBASIS HIJAUAN LOKAL UNTUK KERBAU DI PROVINSI BANTEN - I., Prihantoro; A.T., Aryanto; P.D.M.H., Karti (Pastura, 2019)
Forage is the main feed of buffalo in smallholder farms. The need of forage will increase along to the increased demand of buffalo population. Buffaloes are kept as semi-intensive in natural grassland, house yard and integrated with agricultural land. Forages availability for buffalos are low in the dry season. The aim of this research is to measure the potential forage and the strategy for self-sufficiency of forage for buffalo in Province of Banten. The research was conducted in buffalo pasture (natural and integrated with paddy fields) managed by smallholder farmers in Lebak and Serang Regencies, Banten Province. Parameters measured include: (1) botanical composition of forage, (2) forage carrying capacity, (3) types of feed crops in buffalo pastures, (4) quality of silage and hay products from buffalo pasture. The results showed that botanical composition was varied with predominant vegetation dominance was grasses (56.55-95.94%), low and varied carrying capacity (0.29 ± 0.17 - 0.98 ± 0.39 AU/ha), 24 types of forage plant were found which are potential as buffalo feed. Silage and hay from buffalo grassland were potential as feed resources in the dry season. Keywords: buffalo, natural grassland, self-sufficient feed, smallholder